2014
DOI: 10.1519/jsc.0000000000000368
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of NCAA Division I Collegiate Strength Facilities

Abstract: Strength and conditioning training programs are essential components of athletic performance, and the effectiveness of these programs can be linked to the strength and conditioning facilities (SCFs) used by athletes. The primary purpose of this study was to provide a statistical overview of National Collegiate Athletic Association (NCAA) Division I SCFs, equipment and maintenance budget, and the relationship between SCF budget and staffing space, and equipment. The secondary purpose was to note differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 4 publications
1
17
1
Order By: Relevance
“…Recent investments in athletic training facility renovation were common, with more than 60% of the sample reporting that athletic training facility renovations had been completed within 5 years of the survey. This type of facility investment was consistent with the findings of the exploration of DI strength and conditioning facilities by Judge et al 16 Respondents indicated that another 40% of the schools had received approval to improve some aspect of their athletic training facilities in the near future. Although a majority of athletic training facilities had been improved recently and staff members were positive about the changes to their facilities, the idea that their facilities were meeting the needs of the staff and student-athletes was rated as neutral at all 4 competitive levels.…”
Section: Facilitiessupporting
confidence: 83%
See 4 more Smart Citations
“…Recent investments in athletic training facility renovation were common, with more than 60% of the sample reporting that athletic training facility renovations had been completed within 5 years of the survey. This type of facility investment was consistent with the findings of the exploration of DI strength and conditioning facilities by Judge et al 16 Respondents indicated that another 40% of the schools had received approval to improve some aspect of their athletic training facilities in the near future. Although a majority of athletic training facilities had been improved recently and staff members were positive about the changes to their facilities, the idea that their facilities were meeting the needs of the staff and student-athletes was rated as neutral at all 4 competitive levels.…”
Section: Facilitiessupporting
confidence: 83%
“…These questions were derived from previous work on high school athletic facilities including athletic training areas 17 as well as strength facilities studies at the high school and collegiate levels that assessed facility satisfaction, safety, and adequacy. 16,18 However, neither those studies [16][17][18] nor the present study assessed the validity or reliability of those items.…”
Section: Instrumentationmentioning
confidence: 70%
See 3 more Smart Citations